Repelling the Invasion of the “Other”: Post-Apocalyptic Alien Shooter Videogames Addressing Contemporary Cultural Attitudes - Lizardi, Ryan (Eludamos: Journal for Computer Game Culture, 2009)
In the current videogame landscape, a great deal of first-person shooters are being made that depict a post-apocalyptic invasion by an “alien” force that must be repelled. Culture in a given context can become preoccupied with certain issues and themes because of the societal situation it is born from. This allegorical function serves to speak to historically grounded contemporary concerns. Many of today’s contemporary concerns are related in some ways to 9/11, and the scholarly works that address the influence this event has had on videogames seem to pay closer attention to games that deal with these issues on an explicit level. This analysis moves past the singular historical event of 9/11 to show how latent long term attitudes and beliefs can be addressed by cultural texts on a more allegorical level. Through looking at the FPS invasion videogame texts themselves, such as the Resistance and Killzone series, it becomes clear that what these games are speaking to is a latent fear and mistrust of those culturally different. Through a fair amount of “Othering,” a steadfast ethnocentric viewpoint, and a reliance on the theme of the justified war, these games speak to contemporary cultural attitudes that are intertwined with the reputation of the US overseas. Instead of addressing these concerns head on, these videogame cultural texts place them within thinly veiled allegories that make explicit the desire to repel the invasion of forces that threaten the Western world.